HUBUNGAN PENGETAHUAN PASIEN RAWAT JALAN DENGAN PENGGUNAAN APLIKASI MOBILE JKN DI RSUD OTANAHA - Clara Hijra Audia Hasan; Riska Ahmad; Moh Ichsan Arifin Antu (LPPM STIKES HUSADA JOMBANG, 2025)
Background: The Mobile JKN application is a digital innovation by BPJS Kesehatan designed to simplify public access to the National Health Insurance system. However, its adoption remains limited, partly due to patients’ lack of knowledge regarding the application’s functions and use. Objectives: This study aims to examine the relationship between the knowledge level of outpatients and their use of the Mobile JKN application at RSUD Otanaha in 2025. Methods: This research used a quantitative method with a cross-sectional design. A total of 97 outpatients were selected using the Slovin formula and accidental sampling technique. Data were collected using a structured questionnaire consisting of five indicators: know, comprehension, application, effort expectancy, and performance expectancy. Statistical analysis included univariate description and Pearson correlation to assess the relationship between knowledge and Mobile JKN usage. Results: The study revealed that most respondents rated the Mobile JKN application's efficiency (35.1%) and system availability (41.2%) as “less good,” while 48.5% expressed overall dissatisfaction. Pearson correlation analysis showed a strong and statistically significant relationship between patients’ knowledge and their perception of the application's usability and performance. Specifically, knowledge was strongly correlated with effort expectancy (r = 0.733) and performance expectancy (r = 0.819). Comprehension and application dimensions also demonstrated strong correlations with both effort and performance expectancy (r values ranging from 0.770 to 0.830, p < 0.001). Elderly users experienced more difficulties due to lower digital literacy. Conclusion: There is a significant relationship between patient knowledge and the use of the Mobile JKN application. Knowledge plays a key role in optimizing the application’s utilization. More intensive educational efforts are needed to empower patients to use the app independently as part of improved health service delivery.